USA, China and Global Leadership: Analysis in the Perspective of Conceptualisation. (June 2019) - Sun, Xihui
In recent years, the Trump administration, embracing the principle of 'America First', adopts protectionism, doubts climate change and withdraws from many multilateral regimes in fields of trade, security, politics and global governance, while China firmly supports economic globalisation and free trade, adheres to peaceful development and advocates cooperation, openness, inclusiveness and mutual benefits. In these circumstances, there appears a heated debate on the shift of global leadership in academia and media, focusing on China. Beginning with summing up typical opinions about the issue of global leadership concerning the USA and China, the author conceptualises 'global leadership', analyses the nature and state of USA's global leadership, discusses the Trump administration's foreign policies and USA's global leadership and comments China's views and policies concerning global leadership. This article primarily argues that leadership, unlike hegemony, is not a zero-sum relationship, and there may be more than one country harmoniously and complementarily exerting leading roles in global affairs. Only by clearly differentiating hegemony and leadership can great powers better deal with their relations.